A hangversenyrendezés finanszírozása: egy kutatás tanulságai - Retkes, Attila (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
The author of the paper has done research and analysis related to musical performance - also to certain fields of theatre and dance performance - since 2005. These examinations were above all focusing on economic (financing) problems of the mentioned areas. After the publishing of the book entitled Zene - Művészet, piac, fogyasztás [Music - Art, market, consumerism] in 2010, he pursues his work as the head manager of the Institute for Cultural Analysis Budapest and as a PhD candidate. The present paper is a presentation of his latest qualitative research which concentrates on the work of concert organizers. Examining different sources and means of financing, he concludes that the governmental budget and the National Cultural Fund continue to be determining in Hungarian concert financing. The recourse to the remaining five financing possibilities - European Union, local governmental sector, non governmental organizations, private sector and families - seems to present serious difficulties for various reasons.